Acute and Subchronic Airway Inflammation after Intratracheal Instillation of Quartz and Titanium Dioxide Agglomerates in Mice - Martin Roursgaard; Keld A. Jensen; Steen S. Poulsen; Niels-Erik V. Jensen; Lars K. Poulsen; Maria Hammer; Gunnar D. Nielsen; Søren T. Larsen (The Scientific World Journal)
This study investigated the acute and subchronic inflammatory effects of micrometer-size (micro-size) and nanometer-size (nano-size) particles after intratracheal (i.t.) installation in mice. The role of the type of compound, polymorphism, and size of the particles was investigated. Studied compounds were the two micro-size reference quartzes, SRM1878a and DQ12, a micro- and nano-size rutile titanium dioxide (TiO2), a nano-size anatase, and an amorphous TiO2. Particles were administered by a single i.t. instillation in mice at a fixed dose of 5, 50, and 500 μg, respectively. Inflammation was evaluated from the bronchoalveolar lavage fluid (BALF) content of inflammatory cells, the cytokines tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6), as well as from lung histology. Evaluations were at 24 h (acute effects) and 3 months (subchronic effects) after instillations. Both types of quartz induced a dose-dependent acute increase of neutrophils, IL-6, and total protein in BALF. Limited subchronic inflammation was observed. All types of TiO2 induced a dose-dependent acute increase of neutrophils in BALF. In the acute phase, micro- and nano-size rutile and nano-size amorphous TiO2 induced elevated levels of IL-6 and total protein in BALF at the highest dose. At the nano-size rutile and amorphous TiO2, subchronic lung inflammation was apparent from a dose-dependent increase in BALF macrophages. Histology showed little inflammation overall. The two types of quartz showed virtually similar inflammatory effects. Nearly similar effects were observed for two sizes of rutile TiO2. Differences were seen between the different polymorphs of nano-size TiO2, with rutile being the most inflammogenic and amorphous being the most potent in regard to acute tissue damage.